Penggunaan Sistem Pengendalian Manajemen dalam Meningkatkan Efektivitas Pusat Pertanggungjawaban Keuangan PT. Pertamina (Persero) - Sindi Mayangsari; Nouva Ayu Ramadhanti; Tries Ellia Sandari (GLOBAL SCIENTS PUBLISHER, 2025)
The Management Control System (MCS) functions to ensure that operational activities align with the company’s strategic objectives. In large corporations such as Pertamina, control over financial responsibility centers is essential to maintain efficiency and accountability. This article aims to analyze how Pertamina implements MCS to enhance the effectiveness of financial responsibility centers. The findings indicate that the integration of performance-based budgeting, financial monitoring, internal control, internal audit, and the utilization of financial information systems successfully improves cost efficiency, enhances financial performance achievements, and strengthens transparency and accountability across all Pertamina business units. The results of the study indicate that the Management Control System (MCS) has an influence on the effectiveness of financial responsibility centers.